2019
DOI: 10.1002/ccr3.2383
|View full text |Cite
|
Sign up to set email alerts
|

A case of extreme hyponatremia without neurologic symptoms

Abstract: Our case report highlights that profound hyponatremia with sodium level 101 mmol/L could have no CNS symptoms, and drugs and endocrine disorders are relatively common causes and should be considered in the differential diagnosis of hyponatremia. Standard dose trimethoprim‐sulfamethoxazole‐induced hyponatremia is rare but still worth close attention in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We identified and screened 1,276 studies using the search strategy described in the Methods section. After careful review by 2 independent authors, only 21 studies were included according to the inclusion and exclusion criteria (Table 1 ) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The basic information of 24 patients (10 male and 14 female) is summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified and screened 1,276 studies using the search strategy described in the Methods section. After careful review by 2 independent authors, only 21 studies were included according to the inclusion and exclusion criteria (Table 1 ) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The basic information of 24 patients (10 male and 14 female) is summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Nervous system symptoms are the main clinical manifestations of hyponatremia, ranging from nausea, vomiting, headache and general malaise to changes in mental status, seizures, and even coma [ 12 ]. Our study showed that TMP/SMX-induced hyponatremia mainly manifests as nausea, vomiting, weakness, and fatigue and can also manifest as asymptomatic hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…There are cases of symptomatic hyponatremia following lateral medullar infarct [14]. But there are some rare case reports recording neurologically asymptomatic patients with severe hyponatremia [15].…”
Section: Discussionmentioning
confidence: 99%
“…The vertical dashed and solid lines indicate the respective normal and hypo/hypernatremia [Na + ] that are observed clinically. 93,94 The response sensitivity of R-DiFC to fRBCs over this physiological range was 15.3%. In comparison, using red fluorescence (fig.…”
Section: Cell Sensors In Flow Phantoms In Vitromentioning
confidence: 80%
“…Normal blood sodium levels range between 135 mM and 145 mM. Extreme cases of hyponatremia and hypernatremia are in the range of ~100 mM 93 and ~225 mM, 94 respectively, the former being a potential side effect of lithium that can induce seizures and death. Because of this, some patients under lithium treatment have blood samples drawn weekly to measure sodium levels, but this precludes measurement of more rapid fluctuations in sodium levels over the timespan of hours or days.…”
Section: Introductionmentioning
confidence: 99%